2015
DOI: 10.1126/scisignal.aaa6674
|View full text |Cite
|
Sign up to set email alerts
|

Reelin protects against amyloid β toxicity in vivo

Abstract: Alzheimer's disease (AD) is a currently incurable neurodegenerative disorder and the most common form of dementia in people over the age of 65. The predominant genetic risk factor for AD is the ε4 allele encoding apolipoprotein E (ApoE4). The secreted glycoprotein Reelin, which is a physiological ligand for the multifunctional ApoE receptors Apolipoprotein E receptor 2 (Apoer2) and very low-density lipoprotein receptor (Vldlr), enhances synaptic plasticity. We have previously shown that the presence of ApoE4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 72 publications
2
113
0
Order By: Relevance
“…Mice carrying the loxP-targeted Reln gene (which encodes the protein Reelin) were generated by gene targeting murine SV129J ES cells as described previously (15) and mated with Ldlr −/− (28) mice to yield double homozygotes ( Reln fl/fl ;Ldlr −/− ). Reelin fl/fl ;Ldlr −/− mice were then crossbred with CAG-Cre ETR2 mice (Jackson strain # 004682) to obtain CAG-Cre + Reelin fl/fl ;Ldlr −/− mice and their Cre-negative littermates.…”
Section: Methodsmentioning
confidence: 99%
“…Mice carrying the loxP-targeted Reln gene (which encodes the protein Reelin) were generated by gene targeting murine SV129J ES cells as described previously (15) and mated with Ldlr −/− (28) mice to yield double homozygotes ( Reln fl/fl ;Ldlr −/− ). Reelin fl/fl ;Ldlr −/− mice were then crossbred with CAG-Cre ETR2 mice (Jackson strain # 004682) to obtain CAG-Cre + Reelin fl/fl ;Ldlr −/− mice and their Cre-negative littermates.…”
Section: Methodsmentioning
confidence: 99%
“…This is partially due to the fact that ApoE expression, in both mice and humans, begins relatively late in development [46, 47]. Additionally, adult loss of Reelin and ApoE receptor signaling in mice is well-tolerated in the absence of amyloid pathology, likely due to homeostatic regulation and compensation by other neuromodulatory mechanisms [42]. …”
Section: Reelin Apoe Receptors and Glutamate Signalingmentioning
confidence: 99%
“…Previously, it was difficult to examine this protective role of Reelin in vivo , due to the necessity of Reelin in brain development; however, a conditional knockout mouse was recently developed to overcome these challenges. It was found that while adult loss of Reelin does not cause significant cognitive impairment - suggesting an ability of a healthy CNS to homeostatically compensate for Reelin loss - overexpression of Aβ in Reelin-deficient mice leaves them heavily impaired in the Morris Water maze task of learning and memory [42]. These findings highlight the important role for Reelin and ApoE receptor signaling in protecting the synapse from Aβ-induced suppression.…”
Section: Reelin Apoe Receptors and Glutamate Signalingmentioning
confidence: 99%
“…Previous studies have interrogated the effects of Reelin expression on levels of APP in different model systems [2529]. In addition, connections between Aβ and Reelin have been shown, including effects of Aβ on Reelin signaling [30] and effects of Reelin on Aβ fibril formation and toxicity [3132]. While reports differ on the directionality of these effects in different models, there is consensus that these two proteins interact biochemically.…”
Section: Discussionmentioning
confidence: 99%